Intrinsic, Pro-Apoptotic Effects of IGFBP-3 on Breast Cancer Cells are Reversible: Involvement of PKA, Rho, and Ceramide - Perks, Claire M.; Burrows, Carla; Holly, Jeff M. (Frontiers in Endocrinology, 2011)
We established previously that IGFBP-3 could exert positive or negative effects on cell function depending upon the extracellular matrix composition and by interacting with integrin signalling. To elicit its pro-apoptotic effects IGFBP-3 bound to caveolin-1 and the beta 1 integrin receptor and increased their association culminating in MAPK activation. Disruption of these complexes or blocking the beta 1 integrin receptor reversed these intrinsic actions of IGFBP-3. In this study we have examined the signalling pathway between integrin receptor binding and MAPK activation that mediates the intrinsic, pro-apoptotic actions of IGFBP-3. We found on inhibiting protein kinase A(PKA), Rho associated kinase (ROCK) and ceramide, the accentuating effects of IGFBP-3 on apoptotic triggers were reversed, such that IGFBP-3 then conferred cell survival. We established that IGFBP-3 activated Rho, the upstream regulator of ROCK and that beta1 integrin and PKA were upstream of Rho activation, whereas the involvement of ceramide was downstream. The beta 1 integrin, PKA, Rho and ceramide were all upstream of MAPK activation. These data highlight key components involved in the pro-apoptotic effects of IGFBP-3 and that inhibiting them leads to a reversal in the action of IGFBP-3.